Analisis Waktu Tunggu Pelayanan Resep Non Racikan Pada Pasien Badan Penyelenggara Jaminan Sosial (BPJS) Di Rumah Sakit Harapan Bunda (RSHB) Kota Batam - Nur Wafiq Azizah; Reny Haryani; Desy Maniarti Gusmali; Aprilya Sri Rachmayanti; Nahrul Hasan (STIKes Ibnu Sina Ajibarang, 2023)
One of the Minimum Service Standards for hospital pharmacy is waiting time. Waiting time for drug service is the time from the patient submitting the prescription to receiving the drug. This study aims to analyze the accuracy of waiting time for non-recipe prescription services for BPJS patients at RSHB Pharmacy Batam City in accordance with Kepmenkes Number 129 / Menkes / SK / II / 2008 and determine the factors that cause the length of a prescription service process. This study used purposive sampling method for BPJS patients at RSHB Batam City. This research concludes with a sample size of 187 non-recipe prescriptions. The conclusion of this study is that the average prescription service time is 49.11 minutes, which means that the Batam City RSHB Pharmacy has not met the Minimum Hospital Service Standards